The Modern Techniques in Spatial Analysis to Isolate, Quarantine the Affected Areas and Prevent the Spread of COVID-19 Epidemic - Al-ramahi, Fouad K. Mashee; Shnain, Ali A.; Ali, Abdulrahman B. (Iraqi Journal of Science, 2022)
COVID-19 is a disease caused by a coronavirus spread globally, including in Iraq; infections have appeared on all Iraq lands in varying proportions. Iraq is among the higher infected world countries. Forty-six infections were simulated on 23 March 2020. Injuries on the eastern side of Baghdad city and to the right side of the Tigris River, which divides the city into two parts, are a natural barrier in quarantine and easily control the movement of people from both sides. In this study, a model was considered a scientific and practical method by following the steps of identifying infected people using the best scientific approach for the spatial process to prevent the virus from spreading. Remote sensing techniques were used as simulations of actual reality by depending on databases from the Iraqi government (Crisis Cell Dept.), tabulating data, and projecting them on virtual maps. Theories and statistical methods were applied in geospatial data analysis by managing these tools and capabilities of geographic information systems. The locations of the infected people were identified to control the spread of the Coronavirus. Two primary groups were identified and analyzed according to real spatial analysis techniques to facilitate control of the region in case of increasing numbers of infected people and control of the region’s residents; later, the epidemic broke out. The first group included the regions (New Baghdad, Al-Ghadeer, Al-Zafaraniya, Al-Amin, Al-Amin, and Karrada), and the second group included the regions (the Tariq neighborhood, Sadr City, Al-Kabir, and Al-Ghozlan). Baghdad city was isolated into two parts by a natural barrier: the Tigris River, Baghdad Rusafa in Baghdad, and Al-Karkh. There is another natural barrier if the epidemic is spread more than the normal state: a water channel (Al-Jayesh Channel) and an international highway (Muhammad Al Qasim). These natural measures and barriers are an ideal model for controlling epidemic spreading, optimizing health capabilities and protection teams, and limiting population movement to prevent the spread of the Coronavirus Covid-19.